2011
DOI: 10.5194/acp-11-4073-2011
|View full text |Cite
|
Sign up to set email alerts
|

A simple representation of surface active organic aerosol in cloud droplet formation

Abstract: Abstract. Atmospheric aerosols often contain surface active organics. Surface activity can affect cloud droplet formation through both surface partitioning and surface tension reduction in activating droplets. However, a comprehensive thermodynamic account for these effects in Köhler modeling is computationally demanding and requires knowledge of both droplet composition and component molecular properties, which is generally unavailable. Here, a simple representation of activation properties for surface active… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
113
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(123 citation statements)
references
References 28 publications
(50 reference statements)
10
113
0
Order By: Relevance
“…The model can be used with surface tension data from bulk measurements while maintaining a thermodynamically rigorous description of the surface-to-bulk partitioning process. The developed framework is consistent with, and builds upon similar simplified treatments of the problem that were recently reported in the literature (Topping, 2010;Prisle et al, 2011;Raatikainen and Laaksonen, 2011). The resulting conceptual framework is useful for highlighting several uncertainties that hinder our ability to precisely pinpoint the role of surface tension in cloud droplet activation using current measurement and data analysis approaches.…”
Section: Introductionmentioning
confidence: 57%
“…The model can be used with surface tension data from bulk measurements while maintaining a thermodynamically rigorous description of the surface-to-bulk partitioning process. The developed framework is consistent with, and builds upon similar simplified treatments of the problem that were recently reported in the literature (Topping, 2010;Prisle et al, 2011;Raatikainen and Laaksonen, 2011). The resulting conceptual framework is useful for highlighting several uncertainties that hinder our ability to precisely pinpoint the role of surface tension in cloud droplet activation using current measurement and data analysis approaches.…”
Section: Introductionmentioning
confidence: 57%
“…This is indicative of surfactants being present, as particles activating at higher supersaturations (i.e., smaller particles) tend to be more concentrated in surfactants at the critical wet diameter, resulting in a greater surface tension reduction than in particles which activate at lower supersaturations. This is applicable when surface-bulk partitioning of organics does not fully compensate for surface tension depression (32), and if surfactants are in equilibrium with the bulk and gas phase.…”
Section: Resultsmentioning
confidence: 99%
“…Many organic compounds found in ambient organic aerosol lower the surface tension at the solution-air interface (Tuckermann and Cammenga, 2004;Tuckerman, 2007). However, several studies have demonstrated via experiment and theory that surfactant partitioning between the bulk solution and the Gibbs surface phase greatly diminishes the effect one would predict by applying macroscopic surface tensions in Köhler theory (Li et al, 1998;Rood and Williams, 2001;Sorjamaa et al, 2004;Prisle et al, 2011). Neglecting to account for reduced surface tension and using water activity to estimate CCN activity results in an underestimate of κ by ∼ 30 % for the strong surfactant sodium dodecyl sulfate (Petters and Kreidenweis, 2013).…”
Section: Model Assumptions and Limitationsmentioning
confidence: 99%